2021
DOI: 10.1088/2051-672x/ac0ba1
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of foil air journal bearing employing micro-pocket and textures on top compliant surface

Abstract: Investigations to reduce the friction and improve the dynamic performance of a self-acting air foil journal bearing have been performed and presented herein employing the texture, micro-groove and micro-pocket on the top foil. Significant improvements in the static and dynamic performances have been found in presence of micro-pocketed/grooved and textured top foils in comparison to conventional plain foil. The micro-pocketed top foil yields better performance as compared to textured and conventional cases. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The friction between top foil/bump and bump foil/sleeve foil has been ignored in this work since pocket/texture affects only hydrodynamic friction. 26 The friction force (F s ) can be computed using the expression below…”
Section: Miscellaneous Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The friction between top foil/bump and bump foil/sleeve foil has been ignored in this work since pocket/texture affects only hydrodynamic friction. 26 The friction force (F s ) can be computed using the expression below…”
Section: Miscellaneous Relationsmentioning
confidence: 99%
“…Furthermore, these numerous micro-features of textures trap contaminants/debris while also providing lubrication. 2426…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above mentioned studies have not only demonstrated the influence of texture on the lubricating performance but also shown that the load-carrying capacity is linked to the shape and distribution of the texturing surface. Furthermore, to improve the load-carrying capacity, numerous optimization measures have been proposed in recent years [19][20][21][22]. Shen and Khonsari [20] presented the optimum texture shape for enhancing the load-carrying capacity on parallel surfaces using the sequential quadratic programming(SQP) algorithm: V-shape texture with flat fronts.…”
Section: Introductionmentioning
confidence: 99%
“…Surface texturing means intentionally introducing discrete dimples [10,11], protrusions [12], or continuous grooves [13,14] on the lubricated surface. Given the significant discretization efforts [15] introduced by the above micro-structures in journal bearing and the nonlinearity of the compressible Reynolds lubrication equation, thus the early-stage study about textures mainly focuses on incompressible medium flow systems inside sliding and thrust bearing [15].…”
Section: Introductionmentioning
confidence: 99%